Pengaruh Kapasitas Aparatur Desa terhadap Akuntabilitas Pengelolaan Dana Desa Di Kabupaten Wonogiri dengan Sistem Keuangan Desa sebagai Variabel Intervening - Mufti Arief Arfiansyah (Lisyabab : Jurnal Studi Islam dan Sosial, 2021)
The purpose of this study was to determine how the capacity of the village apparatus affects the accountability of village fund management and to determine whether the Village Financial System acts as an intervening variable. This study applies a quantitative descriptive approach to the population of villages in Wonogiri Regency. The sample was determined by purposive sampling technique. Data collection uses primary data from questionnaire data collection with the village head and village secretary as respondents. Data analysis applies path analysis with SPSS 20 software. Based on the results of the analysis, the research results include 1) The capacity of the village apparatus has a positive and significant effect on the Village Financial System. 2) The Village Financial System affects the accountability of village fund management. 3) The capacity of the village apparatus has a positive and significant effect on the accountability of village fund management. 4) The village financial system intervenes in the influence of the capacity of the village apparatus on the accountability of village fund management.